PENGARUH MODEL STUDENT TEAM ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR IPS PESERTA DIDIK KELAS V - Nursita, Nena (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The influence of the Student Team Achievement Division model on the learning outcomes of IPS students class V. This study aims to find out how big the influence of the Student Team Achievement Division model on the results of IPS learning. The method used in this research is experimental method, with nonequivalen control group design. Collecting technique is measurement technique. Based on result of data analysis, the mean of learning result of student of experiment class equal to 83,85 while control class equal to 77,77. The result of hypothesis test (t-test) using t-test pollad variance was obtained tcount of 2,757 and ttable 1,677 (significance level (α) = 5% and dk = 51) showed that tcount is greater than ttable then Ha is accepted. From the calculation of Effect size, obtained 0.80 (medium criterion) This means talking stick model gives a high influence on the learning outcomes of third grade students of Elementary School 11 Pontianak City. Keywords: Influence, Model Student Team Achievement Division, Learning Outcomes